SVITLANA IVANIVNA DOROSHENKO — an Outstanding Figure in Ukrainian Orthodontics - Saranchuk Олеся; Fedorova Оксана (Actual Dentistry, 2026)
The study of the personalities of leading dental scientists is an important component of the history of medical science in Ukraine. A special place in this context is occupied by the figure of Professor Svitlana Ivanovna Doroshenko, whose scientific and pedagogical activities significantly influenced the formation of orthodontics as an independent branch of dentistry, the development of clinical practice, and the formation of a system of training specialists in Ukraine.